User Benefits of Non-Linear Time Compression - Gupta, Anoop; He, Liwei; He, Li-wei (2000)
In comparison to text, audio-video content is much more challenging to browse. Time-compression has been suggested as a key technology that can support browsing – time compression speeds-up the playback of audio-video content without causing the pitch to change. Simple forms of time-compression are starting to appear in commercial streaming-media products from Microsoft and Real Networks. In this paper we explore the potential benefits of more recent and advanced types of time compression, called non-linear time compression . The most advanced of these algorithms exploit fine-grain structure of human speech (e.g., phonemes) to differentially speed-up segments of speech, so that the overall speed-up can be higher. In this paper we explore what are the actual gains achieved by end-users from these advanced algorithms, and whether the gains are worth the additional systems complexity. Our results indicate that the gains today are actually quite small and may not be worth the additional complexity.